Unilateral asterixis in arm and leg caused by internal capsula stroke - Feil, Katharina; Huber, Marion; Goldschagg, Nicolina; Kellert, Lars (Case reports in neurological medicine, 2018)
We report an unusual clinical manifestation of ischemic stroke with acute right-sided asterixis affecting the arm as well as the leg due to a lesion in the left posterior limb of the internal capsula. After treatment with intravenous thrombolysis the patient made a good recovery. Notably, in this case unilateral asterixis affected the arm as well as the leg, resulting in postural and gait instability. In addition, damage in the basal ganglia-thalamo-cortical network, as in our patient, has to be distinguished from other supratentorial causes of acute asterixis like thalamic or frontal lobe lesions linked to the cerebello-brainstem-thalamo-frontal lobe circuits.
Gesehen am 29.04.2020